Analysis on the Good and Dark Sides of Social Media in Era 4.0 - Tri Yusnanto; Fatkhurrochman; Sugeng Wahyudiono (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
This article explores a discourse on the light and dark side of social media, derived from a variety of studies. It also provides a reflection on the subject. The article uses literature review as a research method to make sense of the collected data. In short, social media is neither beneficial nor harmful; it is not neutral. It is just a support to all that we want to convey. Thus, the light and dark side of social networks can be traced back to how a particular individual uses the platform. It simply becomes beneficial or annoying depending on the user himself. Factors such as, but not limited to, intention, prudence, use and self-control contribute to outcomes, whether positive or negative in nature